The Effects of Official and Unofficial Information on Tax Compliance - Filomena Garcia; Luca David Opromolla; Andrea Vezzulli; Rafael Marques (Center for Economic Studies and ifo Institute (CESifo), 2018)
The administration of tax policy has shifted its focus from enforcement to complementary instruments aimed at creating a social norm of tax compliance. In this paper we provide an analysis of the effects of the dissemination of information regarding the past degree of tax evasion at the social level on the current individual tax compliance behavior. We build an experiment where, for given levels of audit probabilities, fines and tax rates, subjects have to declare their income after receiving either a communication of the official average tax evasion rate or a private message from a group of randomly matched peers about their tax behavior. We use the experimental data to estimate a dynamic econometric model of tax evasion. The econometric model extends the Allingham-Sandmo-Yitzhaki tax evasion model to include self-consistency and endogenous social interactions among taxpayers. We find four main results. First, tax compliance is very persistent. Second, the higher the official past tax evasion rate the higher the degree of persistence: evaders are more likely to evade again, and compliant individuals are more likely to comply again. Third, when all peers communicate to have evaded (complied) in the past, both evaders and compliant individuals are more likely to evade (comply). Fourth, while both treatments, and especially the unofficial information treatment, are associated, in the context of our experiment, with a significantly larger growth in evasion intensity, the aggregate effect depends on the characteristics of the population. In countries with inherently low levels of tax evasion, official information can have beneficial effects by consolidating the behavior of compliant individuals. However, in countries with inherently high levels of tax evasion, official information can have detrimental effects by intensifying the behavior of evaders. In both cases, the impact of official information is magnified in the presence of strong peer effects.
Keywords: H26; D63; C24; C92; Z13; 330; tax morale; information; tax evasion; experiment; peer effects